2002
DOI: 10.1152/ajpregu.00738.2001
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines and chemokine receptors in leukocyte trafficking

Abstract: mokines regulate inflammation, leukocyte trafficking, and immune cell differentiation. The role of chemokines in homing of naive T lymphocytes to secondary lymphatic organs is probably the best understood of these processes, and information on chemokines in inflammation, asthma, and neurological diseases is rapidly increasing. Over the past 15 years, understanding of the size and functional complexity of the chemokine family of peptide chemoattractants has grown substantially. In this review, we first present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
445
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 585 publications
(467 citation statements)
references
References 184 publications
15
445
0
4
Order By: Relevance
“…In response to inflammatory stimuli, they migrate from the circulation to infected tissues, where they protect their host by phagocytosing, killing and digesting bacterial and fungal pathogens. 33,34 Many neutrophil functions are mediated by PtdIns(3,4,5)P3. For example, a variety of chemoattractants such as bacteria-released formyl-peptides, some complement fragments Interestingly, the InsP3 kinase is not constitutively active in neutrophils.…”
Section: Ins(1345)p4 and Insp3kb Regulate Innate Immunity Via Modumentioning
confidence: 99%
“…In response to inflammatory stimuli, they migrate from the circulation to infected tissues, where they protect their host by phagocytosing, killing and digesting bacterial and fungal pathogens. 33,34 Many neutrophil functions are mediated by PtdIns(3,4,5)P3. For example, a variety of chemoattractants such as bacteria-released formyl-peptides, some complement fragments Interestingly, the InsP3 kinase is not constitutively active in neutrophils.…”
Section: Ins(1345)p4 and Insp3kb Regulate Innate Immunity Via Modumentioning
confidence: 99%
“…Peripheral blood leukocytes and those found in secondary lymphoid organs are quite distinct and must express different chemokine receptors and adhesion molecules to be differentially localized during trafficking [7,20]. We examined sulfatide-induced CXCR4 upregulation on the heterogeneous population of leukocytes from various origins and observed detectable CXCR4 up-regulation on leukocytes isolated from the spleen, Peyer's patches, lymph nodes and bone marrow (data not shown); however, this increase was not as large as previously observed on human leukocytes from peripheral blood.…”
Section: Sulfatide Increases Cxcr4 Surface Expression On Murine Leukomentioning
confidence: 99%
“…Macrophages stimulated with CSF-1 show immediate cell polarization, actin reorganization, and migration to the CSF-1 secreting tumor cells [9]. Extensive studies have revealed the molecular mechanism of chemokine receptor, a subfamily of G-protein-coupled receptors, -mediated leukocyte trafficking during inflammation [10,11]. However, the signal transduction pathway that regulates CSF-1-induced macrophage migration is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%